1983
DOI: 10.1007/bf00532484
|View full text |Cite
|
Sign up to set email alerts
|

Extremes and local dependence in stationary sequences

Abstract: Oct EX71MHES AND LOCAL DEPENDENCE IN DISTRIBUTION STATEMENT (of this Report)Approved for public release; distribution unlimited. Extremes; maxima; stationary processes. ABSTRACT (Continue an reverse side if necessary and identify by block numnber)7Extensions of classical extreme value theory to apply to stationary sequences generally make use of two types of dependence restriction: (a) a weak 'mixing condition' restrictine long range dependence; (b) a local condition restricting the 'clustering' of high level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
231
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(234 citation statements)
references
References 13 publications
3
231
0
Order By: Relevance
“…The notion of the EI was latent in the work of Loynes [124] but was established formally by Leadbetter in [122]. The parameter θ quantifies the strength of the dependence of X 0 , X 1 , .…”
Section: Definition 324mentioning
confidence: 99%
“…The notion of the EI was latent in the work of Loynes [124] but was established formally by Leadbetter in [122]. The parameter θ quantifies the strength of the dependence of X 0 , X 1 , .…”
Section: Definition 324mentioning
confidence: 99%
“…A generalization of the GEV theorem holds for time series that are realizations of stationary stochastic processes such that the long-range dependence is weak at extreme levels (Leadbetter 1974(Leadbetter , 1983. In the applications, this property is assumed to hold whenever the block maxima are uncorrelated for sufficiently large block sizes.…”
Section: Gev Modelling For Non-stationary Time Series 3a Stationary mentioning
confidence: 99%
“…It is widely used for analysis of hydrologic extremes (Stedinger and Lu, 1995;Hosking and Wallis, 1996;Katz et al, 2002). This is a continuous distribution with three parameters (location, scale, and shape), and represents the limiting distribution resulting from maxima of identically distributed and independent or weakly dependent random variables (Leadbetter, 1983). In previous studies (Morrison and Smith, 2002;Northrop, 2004;Lima and Lall, 2010;Villarini et al, 2011aVillarini et al, , 2011d, the location and scale parameters were found to scale linearly in the log-log domain (power law behaviour).…”
mentioning
confidence: 99%